4D quantitative proteomics of ovarian granulosa cells reveals the involvement of oxidative phosphorylation in non-elderly women with diminished ovarian reserve - Hong-xing Li; Xiao-ling Ma; Li-li Zhang; Tian-yu Jia; Yi Jin; Shi-long Xue; Ya-Ming Xi (Journal of Ovarian Research)
Abstract Objective This study compared the proteomic differences between non-elderly diminished ovarian reserve (DOR, < 35 years) and normal ovarian reserve (NOR) to better understand the molecular mechanisms behind ovarian reserve changes in Poseidon Group III. Methods: Ovarian granulosa cells (GCs) from infertile women with DOR in Poseidon Group III and women with NOR were analyzed using 4D label-free quantitative proteomics. A comprehensive bioinformatics analysis was performed to identify differentially expressed proteins (DEPs) in order to gain a deeper understanding of the mechanisms underlying DOR. The results were subsequently validated by RT-qPCR and Western blot. Results: In this study, a total of 4,940 proteins were identified. Compared to the NOR group, the non-elderly DOR group showed 63 upregulated proteins and 308 downregulated proteins. Among the differentially expressed proteins, 77 were localized to the mitochondria, representing 28.62% of the total. Key domains, including Pyridine nucleotide-disulfide oxidoreductase, FAD/NAD(P)-binding, and Acyl-CoA dehydrogenase/oxidase C-terminal, showed the highest enrichment in mitochondria, suggesting mitochondrial dysfunction in diminished ovarian reserve. Gene Ontology (GO) analysis indicated that most differential proteins were involved in oxidoreductase activity, immune processes, and coenzyme binding. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis highlighted metabolic pathways and oxidative phosphorylation as the most enriched. Furthermore, it was confirmed that the expression of NDUFS3, NDUFB5, NDUFAF2, UQCRC1, UQCRC2, ATP5L, DAG1, PKM2, and SIRT5 matched the proteomics data. Conclusions: We present the first data on the protein expression profiles in ovarian GCs from NOR and Poseidon Group III patients using 4D proteomics. The proteins identified in this study could serve as potential novel biomarkers for Poseidon Group III patients.